Implementasi Syarat Poligami Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan di Pengadilan Agama Surakarta - Ayu Nopitasari; Anjar Sri Ciptorukmi Nugraheni (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This research aims to find out and analyze the implementation of fulfilling the requirements for polygamy in order to obtain permission from the Surakarta Religious Court. Apart from that, it is also to find out and analyze forms of protection for wives' rights in cases of applications for polygamy permits. This research is empirical legal research with a qualitative approach. The types of data used are primary data and secondary data. The techniques used in collecting legal materials in this research were interviews and literature study. The data analysis technique used in this legal research is a qualitative data analysis technique with an interactive analysis model. Based on this research, the results obtained show that the implementation of polygamy requirements is in accordance with Article 4 paragraph (2) and Article 5 paragraph (1) of Law Number 1 of 1974 concerning Marriage, PP Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law (KHI). If the alternative and cumulative requirements are met, accompanied by perfect evidence, the panel of judges will grant the Petitioner's request for a polygamy permit. The form of protection of the wife's rights in the case of a polygamy permit application at the Surakarta Religious Court is that first, the polygamy permit application case is contentious by placing the wife as the respondent, so the wife has the right and opportunity to respond and submit answers, duplicates and conclusions in front of the court regarding the permit application. polygamy proposed by the husband. Second, there must be a request for determination of joint assets. Determining joint assets is very important to provide certainty about the status of joint assets and at the same time protect the wife's property rights so that they do not get mixed up. Third, namely the marriage agreement, between husband and wife, they can enter into a marriage agreement to guarantee the protection of joint assets. Apart from that, this marriage agreement is not limited to financial or property matters, but also accommodates other issues that are important to be a